Titanium complexes containing tridentate [ONO] type Schiff base ligands for the cycloaddition reaction of CO2 to propylene oxide. (15th February 2018) - Byun, Young Min; Lee, Ji Min; Ryu, Ji Yeon; Go, Min Jeong; Na, Kyung Su; Kim, Youngjo; Lee, Junseong
Graphical abstract: Two new titanium complexes possessing chiral tridentate Schiff base ligands were prepared and used in catalytic reaction of cycloaddition of CO2 to propylene oxide, providing considerable activities. Abstract: New titanium complexes, TiL Cl2 (THF) and TiL 2, containing the tridentate chiral Schiff-base ligand, L, prepared from the condensation reaction of 2, 4-pentadione and (1 R, 2 S )-(−)-1-aminoindanol, were synthesized and characterized by various analytical methods including X-ray crystallography. LigandL acted as a dianionic tridentate ligand and, owing to a chiral center in the aminoindanol part, imparted chirality to its titanium complexes. The newly synthesized titanium complexes and previously reported analogous Ti complexes were used as catalysts in the cycloaddition of CO2 to propylene oxide as the first representatives of titanium complexes with tridentate Schiff base ligands to have been used for this purpose. These complexes provided high selectivity toward cyclic propylene carbonate (>99%) and showed considerable activities with TOF values up to 131 h −1 in comparison with the previously reported catalyst systems.